STUDENTS ATTITUDE TOWARD GOVERMENT SCIENCE AND PUBLIC ADMINISTRATION STUDIES - Fadil, Muhammad (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2016)
The research purpose is to describe students’ attitudes about their major studies in social and political faculty in Universitas Islam ‘45’, which are goverment science (IP) and public administration (IAN). Attitude concern is if they regard that both major have similarities to each other since they have almost same competencies. The attitude levels are affective, cognitive, and behavior as for cognitive is the most dominant level evaluating both majors. This survey research uses descriptive method, with 27 respondents in the process of writing of final research from both major. The result shows positive tendencies from all level of students attitude (mode=4), especially cognitive. It means that both students group (government science =17 and public administration=10) has same attitude concluding that both of major studies are similar. T-test also shows no significant value (p ≥ .05) which means both students group have no differences attitude.